MANAGEMENT OF DEFENSE HERITAGE BASED TOURISM TO ENHANCE YOUTH NATIONALISM AND PATRIOTISM - Herlina JR Saragih; Suhirwan Suhirwan; Aris Sarjito; Yenglis Dongche Damanik; Ni Nyoman Ayu Nikki Avalokitesvari (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Some countries have proven to be advanced by managing their historical and cultural heritage and promoting it internationally. Japan and South Korea are living examples, who transform the war site not only into national defense heritage but also bring it to the international level.  The management of historical heritage is crucial to enhance people's awareness of the importance of national defense. However, many of Indonesia's historical relics are still neglected or poorly managed, even though many historical and cultural heritages have the potential to become tourist attractions. This article aims to discuss how to manage Indonesian historical and cultural heritage to enhance nationalism and patriotism. Proper management of historical and cultural heritage will increase the love of the motherland. The research method is done by a qualitative research method as well as literature studies. This study proves that the management of culture and historical heritage of Indonesia, especially those related to the national struggle, is still largely ignored. Moreover, Indonesia even lacks in managing its historical and cultural heritage. Therefore, Indonesia has to improve the management of its cultural and historical heritage so that it can be promoted to the global world as an object of tourism to increase the nationalism of the younger generation.